Investigating The Impact of Physicians' Attitudes Towards Death And Their Demographic Factors On Disclosure Of Bad News To Cancer Patients - Saba Ebrahimian; Masoomeh Karimi; Danial Fazilatpanah; Dariush Moslemi (Asia Pacific Journal of Health Management)
Background: This study aimed to investigate the attitudes of physicians towards death and cancer patients as well as to examine the relationship between physicians' demographic variables, their death anxiety, their attitudes and avoidance behavior towards informing patients about their diagnoses, and physicians' opinions about the necessity of education on how to approach patients with terminal illness.